SEBARAN DAN PERKIRAAN PRODUKSI PAKAN GAJAH SUMATERA (Elephas maximus sumatranus Temminck.) DI SEKITAR DURI KECAMATAN MANDAU KABUPATEN BENGKALIS - Rahmad Fadillah; Defri Yoza; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Sumatra’s Elephant (Elephas maximus sumatranus) including one of the endangered animals and is the largest animal is still alive and could only be encountered on the island of Sumatra. Form of elephant population dynamics influenced food availability, water availability and mineral salts. The results showed that the sign of Sumatra’s Elephant often encountered in the area of ​​plantations, secondary forests and shrubs. Estimates as many that 49 elephant dung and 2450 pellets with an area of ​​0.02 km² transect. Elephant population density as much as 0,966 head/0,02km2. Estimates of the total number of Sumatran Elephants using dung circumference measurement method (dung) Is estimated at about 20 head. Feed plants identified as many that 29 species of elephants consisting of 16 family. Plant seedlings elephants feed as many that 11 species and 18 herbaceous species. Plants that are found for levels of herbaceous Poaceae and Asteraceae tribe while the seedlings are found plants belonging to the family Myrtaceae, Moraceae, and Euphorbiaceae. Elephant feed production as much as 11,108 kg / ha. Elephant feed requirements with an approximate calculation of the number of elephants 0,48 head / ha requires feed 144 kg / ha. Keywords: elephant, location, population, feed.